Fluidity and time-based architecture : a community centre in Hout Bay harbour - Pilzweger, Sven (School of Architecture, Planning and Geomatics, 2015)
The focus of this dissertation study is Hout Bay harbour and the fluidity thereof - dealing with how the space changes over time. There is an apparent disconnection between space within the harbour, the land and sea, the people frequenting the space, as well as between the harbour and the broader Hout Bay community. The reestablishment of a Hout Bay historical activity route and a new community centre serving as the base for this route seeks to address these issues. In addition, the proposed design will seek to capitalise and improve on the existing fluidity of the harbour's spatial experience.